Immigration and the Rise of American Ingenuity - Akcigit, Ufuk; Grigsby, John; Nicholas, Tom (American Economic Review, 2017)
We build on the analysis in Akcigit, Grigsby, and Nicholas (2017) by using US patent and census data to examine the relationship between immigration and innovation. We construct a measure of foreign born expertise and show that technology areas where immigrant inventors were prevalent between 1880 and 1940 experienced more patenting and citations between 1940 and 2000. The contribution of immigrant inventors to US innovation was substantial. We also show that immigrant inventors were more productive than native born inventors; however, they received significantly lower levels of labor income. The immigrant inventor wage-gap cannot be explained by differentials in productivity.